Permanência e Identidade: Habitar no Centro do Porto - Bárbara Moreira Rato de Sousa Roque (2019)
Faced with the babel of languages and faces that presently enliven thestreets of downtown Porto, the aim here is to understand the impact that thegrowing influx of people has on the city and to discuss how can architecturereact to this new reality.Believing that a local dimension and the proximity between inhabitantsare fundamental for a prospective development of the city, the challenge andthe pertinence of this dissertation arise as a rehearsal of new housing lexiconsthat contemplate different possibilities of permanence as a possible solutionto counteract the growing separation between "the ones from here" and "theones from outside" and, simultaneously, try to propose answers to the housingproblems emerging in the city.